PEMENUHAN HAK NAFKAH ANAK PASCA PERCERAIAN STUDI KASUS DI DESA MULYOREJO KECAMATAN TIRTO KABUPATEN PEKALONGAN - Yana, Lutfi (Al-Hukkam: Journal of Islamic Family Law, 2023)
Livelihood is an expenditure that is usually used by a person for his dependents in meeting the necessities of life, whether in the form of clothing, food or board and others with something good. Making a living after divorce is the responsibility of the husband, but in practice in most societies this obligation is not carried out properly. After a divorce, fathers tend to ignore maintenance for their children, especially those related to the child’s basic rights, this is not in line with what is stipulated in Fiqh, the Marriage Law and the Compilation of Islamic Law. This study aims to find out how the implementation of children’s livelihood rights after divorce in Mulyorejo Village, Tirto District, Pekalongan Regency and the efforts made bay mothers to maintain children’s livelihood right. The type of research used is field research with a qualitative approach. This study uses primary data sources obtained through interviews with informants and secondary data obtained through books, journals or readings related to the research theme. This study uses data analysis techniques in the form of data compilation. Presentation reduction, and drawing conclusions using qualitative descriptive techniques. The results of this study are that the implemention of children’s rights to support after divorce has not been able to be carried out properly. There are several patterns in its implementation, there are always giving, sometimes giving, never giving and naver giving. In this case, there is an affort made by the mother, namely communicating and sending people (children)so that the ex-husband does not forget his obligation to provide a living for the child. But there are also those who do not make any efforts, because they are still able to meet the needs of their children alone.